A PHILOSOPHICAL INQUIRY INTO FEMINIST LITERARY CRITICISM: REPRESENTATIONS OF WOMEN’S CHARACTERS IN SUNDARI MARDJUKI’S GENDUK - Berebon, Charles (Makassar State University, 2024)
The study focuses on the portrayal of female characters as victims of discrimination rooted in gender differences. This research was conducted using a descriptive-qualitative approach combined with feminist literary criticism. The primary objective was to identify and address the core issues highlighted in the text. The main data source for the study is Genduk, a novel by Sundari Mardjuki, while the secondary data comprises relevant theoretical books and research articles. The findings reveal that Genduk contains several themes related to gender-based discrimination, such as stereotyping, the marginalization of women, excessive work burdens, subjugation, and physical abuse.